3-Dimensional Microorifice Fabricated Utilizing Single Undercut Etching Process for Producing Ultrasmall Water and Chitosan Droplets. (24th November 2013) - Lin, Che-Hsin; Lan, Chun-Hung; Yang, Chih-Hui
Abstract : This research reports a microfluidic device for producing small droplets via a microorifice and a T-junction structure. The orifice is fabricated using an isotropic undercut etching process of amorphous glass materials. Since the equivalent hydraulic diameter of the produced microorifice can be as small as 1.1  μ m, the microdevice can easily produce droplets of the size smaller than 10  μ m in diameter. In addition, a permanent hydrophobic coating technique is also applied to modify the main channel to be hydrophobic to enhance the formation of water-based droplets. Experimental results show that the developed microfluidic chip with the ultrasmall orifice can steadily produce water-in-oil droplets with different sizes. Uniform water-in-oil droplets with the size from 60  μ m to 6.5  μ m in diameter can be formed by adjusting the flow rate ratio of the continuous phase and the disperse phases from 1 to 7. Moreover, curable linear polymer of chitosan droplets with the size smaller than 100  μ m can also be successfully produced using the developed microchip device. The microfluidic T-junction with a micro-orifice developed in the present study provides a simple yet efficient way to produce various droplets of different sizes.